Does exercise in hot environmental condition impair detection of erypropoietin doping? - Caillaud, C.; Trout, G.; Howe, C.; Simar, D.; Fatseas, D.; Kazlauskas, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The abuse of recombinant erythropoietin to stimulate red blood cells synthesis and to improve physical performance is a major concern and improving rHuEPO detection is a real challenge. The current detection method approved by the World Anti-Doping Agency (WADA) is based on the analysis of erythropoietin (EPO) isoforms distribution in urine. A concern has recently been raised as whether strenuous prolonged exercise performed in hot environmental conditions may or not alter native EPO synthesis, EPO excretion or urine isoform distribution. This study was designed to test whether intense exhaustive exercise performed in hot condition will: change haematological parameters; modify EPO isoforms distribution in urine; impair rHuEPO detection via increased excretion of basic isoforms and/or increased protein concentration. After an initial maximal exercise test, 6 highly trained cyclists (26.5 (5) yrs, VO2max:61.1 (4) ml/kg/min) performed 1 hour`s cycling at 70% VO2max in the heat (35oC, 40% rh). The participants then started the acclimatisation period: during 6 consecutive days they did 60 min of cycling exercise at 70% VO2max in hot condition. Blood and urine samples were collected pre and 1hr post exercise during the first and the last exercise session. Haematocrit (Hct), Haemoglobine concentration ([Hb]), EPO were measured and ON-hes and OFF-hre models were calculated. Urine was analysed for EPO isoforms according to current recommendations by wada and updated by wada technical document TD2007EPO. Pre acclimatisation, exercise did not significantly changed [Hb], Hct or models scores ([Hb]: 149.7 (13.6) vs 150.8 (7.5) g/l; Hct: 0.459 (0.04) vs 0.461 (0.03); ON-hes: 171 (22) vs 173 (22); OFF-hre: 84.5 (9) vs 86.3 (4). Post acclimatisation all variables declined post exercise ([Hb]: 148.2 (11.4) vs 141.2 (11.6) g/l; Hct: 0.452 (0.04) vs 0.426 (0.03); ON-hes: 171 (17) vs 163 (13); OFF-hre: 78.8 (5) vs 74.1 (9)). None subjects reached critical cut off levels for identification of EPO doping. Our haematological data support previous reports and demonstrate that 6 days of intense exercise in hot condition do not significantly change variables used in the indirect detection of rHuEPO doping. Some of the changes observed are opposite of those expected to be induced by rHuEPO abuse. Results from urine samples were analysed using both the current peak ratio criteria (B2:E) and the older criteria consisting in the percentage of basic isoforms. We did not find any sample approaching the criteria required for the identification of rHuEPO. The results do not support a hypothesis that acute or chronic exercise in hot environment might impair rHuEPO detection through shifts in the distribution of EPO isoforms. In conclusion this study shows that vigorous aerobic exercise performed in the heat for several consecutive days does not lead to false positive cases of EPO doping.